PRISMA: an attempt to improve standards for reporting systematic review and meta-analysis (Italian Journal of Public Health, 2009)
The advent of evidence-based medicine has challenged our understanding on the merits of various sources of information. The opinion of experts has become the lowest level of the hierarchies of evidence, while meta-analysis reaches the top [1]. Meta-analysis is currently the most cited study design in health sciences and, along with systematic review, it has become increasingly important in health care. This is self evident if we consider its use as a starting point for implementing all practice guidelines [2]. A meta-analysis can be defined as the systematic and rigorous quantitative integration of information on the same research question [3,4]. It goes beyond a literature review as it synthesises the results of the individual studies into a new result [5].